Comparison of the effects of four anaesthetics on haematological and blood biochemical profiles in pikeperch (Sander lucioperca L.) - Kristan, Jiri; Stara, Alzbeta; Turek, Jan; Policar, Tomas; Velisek, Josef (Neuro endocrinology letters, 2012)
OBJECTIVES: The objectives of the study were to compare the effects of Propiscin, 2-phenoxyethanol, clove oil and tricaine methane sulphonate (MS 222), anaesthetics frequently used in aquaculture. DESIGN: The haematological and biochemical blood profiles of pikeperch (Sander lucioperca L.) anesthetized with Propiscin (1.5 ml L-1), 2-phenoxyethanol (0.3 ml L-1), clove oil (33 mg L-1), MS 222 (150 mg L-1) and non-anesthetized control group were tested. Each tested group was divided into two subgroups, the first subgroup was sampled in anaesthesia 10 min after application of the anaesthetic and the second one live on 24h. RESULTS: The erythrocyte count and haematocrit was significantly decreased in 2-phenoxyethanol (24 h) compared with control group (CG). The mean corpuscular haemoglobin concentration was significantly increased in 2-phenoxyethanol (10 min), Propiscin (10 min and 24 h) compared to CG. The 2-phenoxyethanol (10 min and 24 h), MS 222 (24 h), clove oil (24 h), and Propiscin (10 min and 24 h) showed significantly lower leukocyte count compared with CG. The level of glucose was significantly (p<0.05) elevated with MS 222 (10 min) and clove oil (10 min) compared with CG. The 2-phenoxyethanol (10 min and 24 h), MS 222 (24 h), clove oil (24 h), and Propiscin (24 h) showed significantly lower (p<0.01) ammonia levels compared with CG. The triacylglycerols was significantly decreased (p<0.01) with Propiscin (10 min and 24 h), MS 222 (24 h), clove oil (24 h) and with 2-phenoxyethanol (24 h) compared with CG. After 24 hours MS 222 (24 h) and Propiscin (24 h) anaesthesia, fish showed significantly lower (p<0.01) concentration of inorganic phosphate compared with CG. CONCLUSIONS: On the basis of this experiment, it appears that clove oil was associated with the lowest effects in pikeperch and therefore would be recommended as an alternative to MS 222, while Propiscin and 2-phenoxyethanol are not suitable for manipulation with pikeperch in aquaculture.
Keywords: počet erytrocytů; Hematocrit; Aquaculture; Aminobenzoates; Esocidae; hematokrit; krevní proteiny; Clove Oil; zvířata; etomidát; Anesthetics; Blood Proteins; okounovití; aminobenzoáty; Perches; hřebíčkový olej; Erythrocyte Count; anestetika; Etomidate; vodní hospodářství; Animals; Ethylene Glycols; ethylenglykoly